Delivery of Arbuscular Mycorrhiza Fungus Spores via Seed Coating with Biodegradable Binders for Enhancement of the Spores Viability and Their Beneficial Properties in Maize - Marwanto, Marwanto; Bustaman, Hendri; Handajaningsih, Merakati; Supanjani, Supanjani; Murcitro, Bambang Gonggo; Salamah, Umi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2020)
biodegradable polymer such as PVA is considered the most promising candidates for developing the sustainable sticker. The objective of this study was to determine the most suitable PVA + TS blends as adhesives agent for AMF spores inoculation via seed coating which can enhance the spores viability and their beneficial properties in maize. The polythene bag experiment was performed in a screen house of the Department of Plant Protection Faculty of Agriculture, University of Bengkulu Indonesia in 2015. Six adhesive blends were employed: 100% PVA + 0% TS, 75% PVA + 25% TS, 50% PVA + 50% TS, 25% PVA + 75% TS, 0% PVA + 100% TS, and no coating. The six experimental treatments were laid out in a completely randomized design with three replications. The results show that root colonization, AMF spore population, and shoot dry weight in 75% PVA + 25% TS were equal to those in 100% PVA. Root colonization, AMF spore population, shoot P content, and shoot P concentration were greater for 50% PVA + 50% TS than 100% PVA, 100% TS, and no coating. A mixture of 50% PVA + 50% TS was considered the preferred sticker. Thus, the tapioca starch can be used to substitute 25 - 50% of the PVA used without reducing AMF inoculant adhering to seed.Keywords: polymeric seed coating, seed coating formulation, arbuscular mycorrhizal fungi, sustainable coating adhesive, seed inoculation, seed inoculant